Knee joint function in healthy and ACL-reconstructed collegiate female lacrosse players: a pilot study - Peel, S. A.; Walck, C. D.; Taylor, J. B.; Nguyen, A. D.; Westbrook, A. E.; Alfred, E.; Mahon, M.; Ford, K. R. (Journal of Science in Sport and Exercise, 2024)
Purpose To investigate knee joint function during an unanticipated cutting task between healthy and ACL-reconstructed (ACL-R) females within the same NCAA Division I collegiate female lacrosse team (WLAX) via knee mechanics and estimated vasti and hamstring muscle forces.